2011
DOI: 10.1007/s00586-011-1985-1
|View full text |Cite
|
Sign up to set email alerts
|

Change in Cobb angle of each segment of the major curve after posterior vertebral column resection (PVCR): a preliminary discussion of correction mechanisms of PVCR

Abstract: Introduction Posterior vertebral column resection (PVCR) is an effective technique for treating severe rigid spinal deformities, and no other osteotomy is capable for such an excellent corrective effects. The purpose of this study was to discuss the correction mechanisms of PVCR. Materials and methods Forty-six patients with severe rigid spinal deformities undergoing PVCR were retrospectively analyzed. According to a routine posteroanterior supine entire spine radiograph performed before and after surgery, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
(15 reference statements)
0
14
0
Order By: Relevance
“…We believed that by provisional instrumentation, in situ contouring the rod, changing the rod alternatively during correction to maintain the stabilization of the entire spinal column and avoiding sudden displacement of the spinal cord, and by proper and timely shortening the spinal cord to reducing the tension of the cord is important. Based on our intraoperative observation, for patients without preoperative neurological deficits, reverse angulation of the dural sac \20°compared with the previous status is acceptable, and shortening of not more than 3 cm or rotation within 10°of the dural sac will not affect the function of the cord [26]. In our study, level of vertebrae resected and number of segmental vessels ligated was correlated.…”
Section: Operational Factorsmentioning
confidence: 71%
“…We believed that by provisional instrumentation, in situ contouring the rod, changing the rod alternatively during correction to maintain the stabilization of the entire spinal column and avoiding sudden displacement of the spinal cord, and by proper and timely shortening the spinal cord to reducing the tension of the cord is important. Based on our intraoperative observation, for patients without preoperative neurological deficits, reverse angulation of the dural sac \20°compared with the previous status is acceptable, and shortening of not more than 3 cm or rotation within 10°of the dural sac will not affect the function of the cord [26]. In our study, level of vertebrae resected and number of segmental vessels ligated was correlated.…”
Section: Operational Factorsmentioning
confidence: 71%
“…Seven studies were excluded for insufficient number of patients (less than 10 patients) and one study was excluded due to the fact that the ''modified PVCR'' was performed. Seventeen studies from seven institutions [7,[9][10][11][13][14][15][16][17][18][19][20][21][22][23][24][25] were included for further analysis. To avoid overlap of patients in different studies, only one main publication from each institution was retained.…”
Section: Resultsmentioning
confidence: 99%
“…Biomechanical and pathomechanical studies have demonstrated that intact middle and posterior column structures play a key role in spinal stability (21). Xie et al (22) noted that the posterior spinal column was critical for maintaining spinal stability and resistance to shear force and rotational force. Similarly, Degreif et al (23) reported that laminectomy caused 27% rotational stability loss.…”
Section: Discussionmentioning
confidence: 99%